Forearmed : A History of the Intelligence Corps - Clayton, Anthony (London Brassey's (UK) Ltd., 1993)
The word "intelligence" has always cared with it an aura of mystery and its own mythology. The history of the Intelligence Corps leaves not doubt that despite the inescapable need for the tightest security over most intelligence activities, these have grown in the late-19th and 20th centuries to assume an importance which must rank alongside any other military resources in a nation's armory. This study traces the development of the Intelligence Corps, from the birth pangs during World War I, through the struggle for survival between the wars, to the triumphs of World War II and beyond. Two major points emerge in this story - the sheer scale of intelligence operations between 1939 and 1945, and the intellectual quality of the officers and men who were responsible for them. The move to more open government has made possible the release of a welter of information for public consumption, which until recent years has been jealously guarded, making possible the writing of this work.
Include Illustrations, Appendices, Notes and Index.
Distributed in North America to booksellers and wholesalers by the Macmillan Pub. Co., 1993.
Keywords: Military intelligence -- Great Britain -- Great Britain, Army, Intelligence Corps -- World War (1914-1918) -- World War (1939-1945)